2018
DOI: 10.1002/ejhf.1220
|View full text |Cite
|
Sign up to set email alerts
|

Correlation with invasive left ventricular filling pressures and prognostic relevance of the echocardiographic diastolic parameters used in the 2016 ESC heart failure guidelines and in the 2016 ASE/EACVI recommendations: a systematic review in patients with heart failure with preserved ejection fraction

Abstract: Only a small number of studies validated the use of echocardiographic parameters at rest in patients with HFpEF. The best established parameter appears to be E/e', but the existing data only show modest correlations of E/e' with invasive filling pressures and outcomes in HFpEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 45 publications
4
133
2
1
Order By: Relevance
“…However, given the paucity of available studies, the incremental value of LA functional indices in discrimination of HFpEF diagnosis or prognosis above and beyond existing risk stratification models comprising clinical characteristics and/or other echocardiographic data has not yet been studied, and should be the focus of future research. Recent studies have also shown echocardiographic measures of LV diastolic function to be correlated to invasive haemodynamic measures and outcomes in HFpEF . Similar studies assessing the correlation of echocardiographic LA functional parameters with invasively measured parameters could provide additional insights and should be undertaken.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, given the paucity of available studies, the incremental value of LA functional indices in discrimination of HFpEF diagnosis or prognosis above and beyond existing risk stratification models comprising clinical characteristics and/or other echocardiographic data has not yet been studied, and should be the focus of future research. Recent studies have also shown echocardiographic measures of LV diastolic function to be correlated to invasive haemodynamic measures and outcomes in HFpEF . Similar studies assessing the correlation of echocardiographic LA functional parameters with invasively measured parameters could provide additional insights and should be undertaken.…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies have also shown echocardiographic measures of LV diastolic function to be correlated to invasive haemodynamic measures and outcomes in HFpEF. 39,40 Similar studies assessing the correlation of echocardiographic LA functional parameters with invasively measured parameters could provide additional insights and should be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…SOBOTA‐HF study will, with comprehensive transthoracic echocardiography and external independent core echocardiography laboratory centre, be able to investigate the prevalence of three HF phenotypes per LVEF. For the purposes of the primary endpoint, we will apply the ESC guidelines criteria; nonetheless, we will also adopt other criteria for diagnosis of diastolic dysfunction, which will allow the comparison of different approaches, also in conjunction with different natriuretic peptide cut‐offs to suggest the optimal practice to be adopted in daily routine …”
Section: Discussionmentioning
confidence: 99%
“…We studied 143 consecutive patients with clinical and echocardiographic signs of HF (NYHA class 1‐III) diastolic dysfunction and LV EF (≥45%), according to 2016 ESC Heart Failure Guidelines . Forty‐one healthy gender‐ and age‐matched subjects served as controls.…”
Section: Methodsmentioning
confidence: 99%
“…We studied 143 consecutive patients with clinical and echocardiographic signs of HF (NYHA class 1-III) diastolic dysfunction and LV EF (≥45%), according to 2016 ESC Heart Failure Guidelines. 26 Forty-one healthy gender-and age-matched subjects served as controls. Patients were divided into those with (n = 40) or without RV (n = 103) dysfunction according to the echocardiographic parameters previously used.…”
Section: Study Populationmentioning
confidence: 99%